Instruments of health and harm: how the procurement of healthcare goods contributes to global health inequality - Trueba, Mei L; Bhutta, Mahmood F; Shahvisi, Arianne (Journal of medical ethics, 2021)
Many healthcare goods, such as surgical instruments, textiles and gloves, are manufactured in unregulated factories and sweatshops where, amongst other labour rights violations, workers are subject to considerable occupational health risks. In this paper we undertake an ethical analysis of the supply of sweatshop-produced surgical goods to healthcare providers, with a specific focus on the National Health Service of the United Kingdom. We contend that while labour abuses and occupational health deficiencies are morally unacceptable in the production of any commodity, an additional wrong is incurred when the health of certain populations is secured in ways that endanger the health and well-being of people working and living elsewhere. While some measures have been taken to better regulate the supply chain to healthcare providers in the UK, further action is needed to ensure that surgical goods are sourced from suppliers who protect the labour and occupational health rights of their workers.